Strategi Marketing Mix Pada Badan Usaha Batako Gaba - Kiki Novita Sari (Robust: Research of Business and Economics Studies, 2023)
This study aims to discover the marketing mix strategy used by business entities of Gaba Brick consisting of Product, Price, Place and Promotion. This study uses qualitative research methods with descriptive analysis types. This study uses interviews, documentation and observation methods for data collection. Then the data is reduced, presented and then drawn the conclusions. This study shows that business entities of Gaba Brick use the 4p marketing mix strategy. For their products, they are always consistent in quality and service. In terms of price, they apply quite competitive prices, and in terms of location and distribution, they are quite strategic and distribute quite a lot of goods outside the area. lastly, in terms of promotion, they use social media and also word-of-mouth promotion.